Die eiszeitlichen und nacheiszeitlichen Klimaschwankungen im zentralmexikanischen Hochland und ihre Ursachen - Klaus, Dieter (ERDKUNDE, 1973)
The ’glacier pool’, the contemporary glaciers in the Sierra Nevada, is strongly determined by the level of summer precipitation totals. The fact that, despite lower temperatures, there were no glacier advances in the Mexican Highlands during high glacial times, can be traced back to a decrease in summer precipitation amounts and a contemporaneously constant level of winter precipitation. This phenomenon can be explained by the particular geographical situation of Mexico with respect to the high-level trough of low pressure in the lee of the Rocky Mountains. During the Ice Age this through, because of the inland glaciation of North America, was positioned all the year round at about 25-30° northern latitude in the lee of the Rocky Mountains. The beginning of worldwide temperature increases in late and postglacial times led in Mexico to repeated glacier advances. These are explicable in terms of an increase in summer precipitation in conjunction with a northward shift of the trough consequent on ice retreat on the European and north American continents. The glacier advances of the most recent period are probably connected with persistent ’low index circulations’ on the entire northern half of the globe, released by energy transport in the southern hemisphere.